A hydroxylated acrylic resin suitable for solar photovoltaic panel backplane coating and its preparation process
Through the combination of raw materials and process steps of specific ratios, a hydroxyacrylic resin suitable for solar photovoltaic panel back panel was designed, solving the problems of under-compliance of performance and high cost in the prior art, and achieving high performance and low cost coating effects.
Patent Information
- Application Number
- CN202410736971.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-06-07
AI Technical Summary
The prior art is difficult to provide a hydroxyacrylic resin with excellent performance suitable for solar photovoltaic panel back panels, especially with challenges in cost and supply.
Through a combination of raw materials with a specific ratio, a hydroxyacrylic resin suitable for solar photovoltaic panel backsheet coating is designed, which includes a kettle base, mixed monomer dropping material, replenishment and dilute material, and is prepared by specific process steps.
It has achieved stable and excellent coating performance in different climates and environments, and has a variety of resistances (cold resistance, heat resistance, triple protection, weather resistance, etc.) and flexibility, reducing manufacturing costs and improving international market competitiveness.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to a hydroxy acrylic resin suitable for solar photovoltaic panel back plate coating and a preparation process thereof, belonging to the technical field of hydroxy acrylic resin and a preparation process thereof. Background Art
[0002] When the surface of an object needs to be protected and decorated, choosing to use paint to form a coating is a common and relatively economical and practical method.
[0003] The idea and measures of human beings to use solar energy have been around for a long time. In the near future, fossil fuels are on the verge of exhaustion and rising costs. Making full use of solar energy to benefit society is a wise and promising choice and path. At present, the most commonly used way to use solar energy is to generate electricity with photovoltaic panels. Photovoltaic panels are a composite material or a device made of composite materials, consisting of a frame, a backplane (or back film), EVA film, crystalline silicon cells, front glass, etc. The materials of the backplane (or film) of solar photovoltaic panels include KPC (polyvinyl chloride material), KPF (PVDF / PET / fluorine film), TPC (thermoplastic polycarbonate), TPE (thermoplastic elastomer), CPC (chlorinated polyethylene synthetic plastic), etc. There are many types of backplane materials. The function of the backplane is to resist the erosion of the battery panel, film, etc. by the environment such as humidity, heat, and cold, and play the role of corrosion resistance, weather resistance, oxidation resistance and insulation protection, effectively extending the service life of the components. In order to enhance the UV resistance, water resistance, humidity resistance, wind and sand resistance of the backplane, a coating with excellent performance should be applied to the backplane.
[0004] There are many types of high molecular film-forming polymers for coatings, the most common ones are alkyd resins, acrylic resins, polyester resins, amino resins, polyurethane curing agents, epoxy resins, silicone resins, etc. Due to the differences in coating properties, usage environments and construction processes, choosing the right resin is a key factor in creating a coating with unique properties that meets the performance requirements of solar photovoltaic panel backplane coatings.
[0005] Solar back panel coatings should have a series of characteristics such as weather resistance, moisture resistance, severe cold resistance, water resistance, insulation, and resistance to wind and sand friction. They should also be adaptable to a variety of organic and even inorganic materials, have very strong adhesion, and be rolled on a flat surface to form a film of uniform thickness. The drying method of the coating is not suitable for high-temperature baking, and it should be quickly dried at medium and low temperatures. To meet the requirements of coating construction (usually rolling) and coating characteristics at the same time, the quality requirements of the coating are extremely high. The quality of the coating is mainly determined by the film-forming material. According to experience and theoretical knowledge, only hydroxyl acrylic resins with excellent performance combined with weather-resistant curing agents can achieve the expected design effect.
[0006] At present, there are many varieties of hydroxyl acrylic resins on the market, which are mainly used in industrial coatings such as automotive coatings, mechanical coatings, etc. If the hydroxyl acrylic resin used in automotive coatings is used to make PU-type two-component acrylic polyurethane coatings, although its weather resistance is very good, it cannot meet the requirements of adhesion, medium resistance, scratch resistance, and heat resistance of the backplane of solar photovoltaic panels; if water-based hydroxyl acrylic resin is selected, the PU-type water-based two-component polyurethane coatings made of it not only have very harsh construction requirements, but also are prone to coating film morbidity, and are expensive, and their application characteristics cannot meet the requirements of solar photovoltaic panel backplane coatings; for example, the PU two-component coatings made of hydroxyl acrylic resins used in mechanical coatings are far from meeting the requirements of solar photovoltaic panel backplane coatings for application performance. However, the application characteristics of PU-type two-component acrylic polyurethane coatings made of some special hydroxyl acrylic resins imported from abroad can meet the requirements of photovoltaic panel backplane coatings, but the price of such imported special hydroxyl acrylic resins is very expensive, and the supply in China is often limited and cannot be delivered in time.
[0007] Therefore, it is urgent to design a hydroxylated acrylic resin suitable for solar photovoltaic panel backplane coating that can solve the above technical problems. Summary of the invention
[0008] The purpose of the present invention is to solve the deficiencies of the above-mentioned prior art and to provide a hydroxy acrylic resin suitable for solar photovoltaic panel backplane coating and a preparation process thereof, which can achieve excellent coating performance regardless of the environment of the solar photovoltaic panel backplane or the substrate used.
[0009] The hydroxy acrylic resin suitable for solar photovoltaic panel backplane coating of the present invention is special in that it comprises the following raw materials in parts by weight:
[0010] Kettle bottom material: 28-37 parts of butyl acetate, 3-6 parts of propylene glycol methyl ether acetate;
[0011] Mixed monomer drop feed: 13-18 parts of methyl methacrylate, 8-13 parts of n-butyl methacrylate, 7-10 parts of hydroxyethyl methacrylate, 5-8 parts of tert-butyl acrylate, 3-5 parts of lauryl methacrylate, 3-5 parts of isooctyl methacrylate, 0.1-0.3 parts of methacrylic acid, 0.2-0.4 parts of 1,1-bis(tert-butylperoxy)cyclohexane, 0.1-0.2 parts of tert-butyl peroxybenzoate, 2-4 parts of butyl acetate;
[0012] Supplementary material 1: 0.1-0.15 parts of tert-butyl perbenzoate and 1-2 parts of butyl acetate;
[0013] Supplementary material 2: 0.08-0.15 parts of 1,1-bis(tert-butylperoxy)cyclohexane and 1-2.0 parts of butyl acetate;
[0014] Supplementary material 3: 0.08-0.15 parts of 1,1-bis(tert-butylperoxy)cyclohexane and 1-2.0 parts of butyl acetate;
[0015] Diluent: 3-7 parts of butyl acetate.
[0016] A preparation process of a hydroxy acrylic resin suitable for a solar photovoltaic panel backplane coating, which is special in that it comprises the following steps:
[0017] 1) Add the bottom material into the reactor, stir evenly, raise the reflux temperature of the reactor to 130±5℃, keep it for 10-20 minutes, and prepare to drop the mixed monomer drop material;
[0018] 2) Add the mixed monomer dropwise at a uniform speed over 3-3.5 hours, and keep it under reflux for 1.0 hour after the addition, with the temperature controlled at 130±5℃;
[0019] 3) Add additional material 1 dropwise over 30 minutes, and keep it under reflux for 1.0 hour after the addition is completed. The temperature is controlled at 130±5℃;
[0020] 4) Add additional material 2 dropwise over 15 minutes, and keep it under reflux for 2.0 hours after the addition is completed. The temperature is controlled at 130±5℃;
[0021] 5) Add additional material 3 dropwise over 15 minutes, and keep it under reflux for 2.0 hours after the addition is completed. The temperature is controlled at 130±5℃;
[0022] 6) Cool down to 100±5℃, add the diluent, stir evenly and then test the solid content and viscosity to the qualified range. The qualified range is: solid content: 50±2%, viscosity: 3000-5000CPS / 25℃, acid value: ≤3 mgKOH.
[0023] The specific process of detecting the solid content and viscosity is: first measure the solid content. If the solid content is qualified, the viscosity is also qualified. If the solid content does not meet the standard, continue to heat up to the reflux temperature of 130±5°C, maintain, measure the solid every 30 minutes until the solid content meets the standard, then cool down to 100±5°C, and then add the dilution solvent.
[0024] The hydroxy acrylic resin suitable for solar photovoltaic panel backplane coating of the present invention has the following raw material functions and effects:
[0025] 1. Butyl acetate, propylene glycol methyl ether acetate: bottom solvent, used to dissolve and dilute materials, the solvent azeotropic point is suitable for the half-life temperature of the mixed initiator;
[0026] 2. Methyl methacrylate: hard monomer, increases hardness and weather resistance;
[0027] 3. Butyl methacrylate: increases adhesion, increases weather resistance, medium hardness monomer;
[0028] 4. Hydroxyethyl methacrylate: functional monomer, provides hydroxyl groups during film-forming cross-linking, increases weather resistance, and cross-links quickly with curing agent;
[0029] 5. Tert-butyl acrylate: A monomer with suitable hardness and softness, which improves heat resistance and medium resistance (mainly moisture and heat resistance), adhesion and wettability to pigments, and reduces resin viscosity. It contains an "umbrella-shaped" tert-butyl group with a special structure.
[0030] 6. Lauryl methacrylate: soft monomer, increases adhesion, flexibility, water resistance, weather resistance, and contains long-chain groups in the side chain to improve water resistance;
[0031] 7. Isooctyl methacrylate: a softer monomer that increases adhesion, weather resistance, flexibility and water resistance, and the side chain contains a longer hydrophobic group;
[0032] 8. Methacrylic acid: functional monomer, increases adhesion and improves the wetting and dispersibility of pigments and fillers;
[0033] 9. 1,1-Bis(tert-butylperoxy)cyclohexane: initiator, liquid type, high efficiency, half-life temperature 105℃ / 1 hour, 128℃ / 0.1 hour, high resin transparency;
[0034] 10. Tert-butyl perbenzoate: initiator, liquid type, half-life temperature 122℃ / 1 hour, 142℃ / 0.1 hour, high efficiency;
[0035] 11. A small amount of butyl acetate in the dripping material: used for flushing the batching pipeline;
[0036] 12. Tert-butyl perbenzoate in the supplementary feed: i.e., the added initiator, which increases the monomer conversion rate;
[0037] 13. 1,1-bis(tert-butylperoxy)cyclohexane in the additional feed: i.e., the additional initiator, which increases the monomer conversion rate;
[0038] 14. Butyl acetate in the supplementary material: used to dilute the initiator and make the reaction stable;
[0039] 15. Butyl acetate in the diluent: dilute the resin and reduce the low temperature.
[0040] The resin of the present invention is used for solar photovoltaic panel backplane coatings. The base material is usually a composite plastic. The resin must have excellent adhesion to the base material and the prepared coating film has multiple resistances (cold resistance, heat resistance, three-proof, weather resistance, etc.) and certain flexibility. The present invention obtains the desired resin properties by cleverly combining raw materials with various different properties. The functions of the main raw materials are as follows: methyl methacrylate provides hardness and weather resistance; n-butyl methacrylate: provides medium hardness, excellent adhesion to the substrate and weather resistance; hydroxyethyl methacrylate contains hydroxyl functional groups, which are used for condensation polymerization with the NCO functional groups of the curing agent to form a three-dimensional network. It is a functional monomer with excellent weather resistance and high hardness with methyl; tert-butyl acrylate has a certain flexibility and also provides adhesion and heat resistance; lauryl methacrylate and isooctyl methacrylate are soft monomers, and the side chains are on the carbon chains respectively, providing good flexibility and water and cold resistance; the methacrylic acid side chain carries a carboxyl group, which increases adhesion and wettability to pigments; when several monomers are combined, the superimposed characteristics are much higher than one or a few, and the manifestation of the superimposed characteristics is related to the type and quantity of raw materials used. Since it is used in solar photovoltaic panel backplane coatings, the photovoltaic panel backplane is a different plastic with low surface tension, so the methacrylic acid content is relatively low.
[0041] First, the theoretical calculation of the monomers of this combination was carried out. The designed theoretical glass transition temperature of the resin (referring to the solid) is: 28-35℃, and the theoretical hydroxyl value of the resin (referring to the solid) is: 75±5mgKOH / g
[0042] Secondly, according to the application requirements, the technical indicators of the resin are set: 1. Appearance: clear and transparent (visual); 2. Color: <1# (iron-cobalt colorimetry); 3. Solid content: 50±1% (125℃×1h); 3. Viscosity: 3000-5000CPS / 25℃, 3. Acid value: ≤3mgKOH / g; Number average molecular weight: 30000±500
[0043] The coating for the back sheet of solar photovoltaic panels made of hydroxyl acrylic resin with the above-mentioned raw material combination, design parameters and technical indicators has good performance in different climatic environments, and the coating film performance is stable and excellent. It has replaced similar products such as those of Japan's Mitsubishi Corporation, greatly facilitating the demand of domestic customers for such resins, while also reducing the cost of manufacturing such coatings, and has made certain contributions to reducing costs and improving economic benefits in the use of new materials and new energy in my country. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Embodiment 1:
[0046] A hydroxy acrylic resin suitable for a solar photovoltaic panel backplane coating in this embodiment includes the following raw materials in parts by weight:
[0047] Bottom material: 29 g butyl acetate, 4 g propylene glycol methyl ether acetate;
[0048] Mixed monomer drop feed: 14 g methyl methacrylate, 8.5 g n-butyl methacrylate, 7.5 g hydroxyethyl methacrylate, 6 g tert-butyl acrylate, 3 g lauryl methacrylate, 3 g isooctyl methacrylate, 0.1 g methacrylic acid, 0.2 g 1,1-bis(tert-butylperoxy)cyclohexane, 0.1 g tert-butyl peroxybenzoate, 2 g butyl acetate;
[0049] Supplementary material 1: tert-butyl perbenzoate
[0050] Butyl acetate 2 g;
[0051] Additional feed 2: 1,1-bis(tert-butylperoxy)cyclohexane 0.08 g,
[0052] Butyl acetate 1 g;
[0053] Additional feed 3: 1,1-bis(tert-butylperoxy)cyclohexane 0.08 g,
[0054] Butyl acetate 1 g;
[0055] Diluent: 4 grams of butyl acetate.
[0056] A preparation process of a hydroxy acrylic resin suitable for solar photovoltaic panel coatings in this embodiment includes the following steps:
[0057] 1) Add the bottom material into the reactor, stir evenly, raise the reflux temperature of the reactor to 130±5℃, keep it for 10-20 minutes, and prepare to drop the mixed monomer drop material;
[0058] 2) Add the mixed monomer dropwise at a uniform speed over 3-3.5 hours, and keep it under reflux for 1.0 hour after the addition, with the temperature controlled at 130±5℃;
[0059] 3) Add additional material 1 dropwise over 30 minutes, and keep it under reflux for 1.0 hour after the addition is completed. The temperature is controlled at 130±5℃;
[0060] 4) Add additional material 2 dropwise over 15 minutes, and keep it under reflux for 2.0 hours after the addition is completed. The temperature is controlled at 130±5℃;
[0061] 5) Add additional material 3 dropwise over 15 minutes, and keep it under reflux for 2.0 hours after the addition is completed. The temperature is controlled at 130±5℃;
[0062] 6) Cool down to 100±5℃, add the diluent, stir evenly and then test the solid content and viscosity to the qualified range. The qualified range is: solid content: 50±2%, viscosity: 3000-5000CPS / 25℃, acid value: ≤3 mgKOH / g.
[0063] The specific process of testing solid content and viscosity is as follows: first measure the solid content. Under normal circumstances, if the solid content is qualified, the viscosity is also qualified. If the solid content does not meet the standard, continue to heat the reflux temperature to 130±5℃, maintain it, measure the solid every 30 minutes until the solid content meets the standard, then cool down to 100±5℃ and add dilution.
[0064] The test results of Example 1:
[0065] 1. The test results of the resin technical indicators of this embodiment are as follows: solid content 50.5%, viscosity: 4500 CPS / 25°C, acid value: 1.8 mgKOH / g.
[0066] 2. Carry out paint application experiments according to the previous table, and all meet the requirements.
[0067] 3. Synthesis mechanism: Solution-based free radical polymerization reaction uses the "hunger" dropping method to make the molecular weight as uniform as possible. The appropriate dropping time is selected according to the solid content. Too long will affect the production efficiency, and too short will affect the conversion rate. The initiator is added three times to fully improve the conversion rate. After actual measurement, the conversion rate reached 100%.
[0068] 4. The monomer conversion rate is the main factor in process control, which is reflected by measuring the solid content and viscosity. This is because free radical reaction is an irreversible reaction. Usually, when there is more initiator, the resin has a lower viscosity and a lower molecular weight; when there is less initiator, the resin has a higher viscosity and a higher molecular weight; when the reaction temperature is high, the molecular weight is lower and more uniform.
[0069] Embodiment 2:
[0070] The present embodiment provides a hydroxyl acrylic resin suitable for a solar photovoltaic panel backplane coating, comprising the following raw materials in parts by weight:
[0071] Bottom material: 32 g butyl acetate, 5 g propylene glycol methyl ether acetate;
[0072] Mixed monomer drop feed: 16 g methyl methacrylate, 10 g n-butyl methacrylate, 9 g hydroxyethyl methacrylate, 7 g tert-butyl acrylate, 4 g lauryl methacrylate, 4 g isooctyl methacrylate, 0.2 g methacrylic acid, 0.3 g 1,1-bis(tert-butylperoxy)cyclohexane, 0.15 g tert-butyl peroxybenzoate, 3 g butyl acetate;
[0073] Supplementary material 1: tert-butyl perbenzoate 0.12 g
[0074] Butyl acetate 3 g;
[0075] Additional feed 2: 0.1 g of 1,1-bis(tert-butylperoxy)cyclohexane,
[0076] Butyl acetate 1.5 g;
[0077] Additional feed 3: 0.1 g of 1,1-bis(tert-butylperoxy)cyclohexane,
[0078] Butyl acetate 1.5 g;
[0079] Diluent: 5 grams of butyl acetate.
[0080] A preparation process of a hydroxy acrylic resin suitable for solar photovoltaic panel coatings in this embodiment includes the following steps:
[0081] 1) Add the bottom material into the reactor, stir evenly, raise the reflux temperature of the reactor to 130±5℃, keep it for 10-20 minutes, and prepare to drop the mixed monomer drop material;
[0082] 2) Add the mixed monomer dropwise at a uniform speed over 3-3.5 hours, and keep it under reflux for 1.0 hour after the addition, with the temperature controlled at 130±5℃;
[0083] 3) Add additional material 1 dropwise over 30 minutes, and keep it under reflux for 1.0 hour after the addition is completed. The temperature is controlled at 130±5℃;
[0084] 4) Add additional material 2 dropwise over 15 minutes, and keep it under reflux for 2.0 hours after the addition is completed. The temperature is controlled at 130±5℃;
[0085] 5) Add additional material 3 dropwise over 15 minutes, and keep it under reflux for 2.0 hours after the addition is completed. The temperature is controlled at 130±5℃;
[0086] 6) Cool down to 100±5℃, add the diluted material, stir evenly and test the solid content and viscosity to the qualified range. The qualified range is: solid content: 50±2%, viscosity: 3000-5000CPS / 25℃, acid value: ≤3 mgKOH / g
[0087] The specific process of testing solid content and viscosity is: first measure the solid content. Under normal circumstances, if the solid content is qualified, the viscosity is also qualified. If the solid content does not meet the standard, continue to heat the reflux temperature to 130±5℃, maintain it, measure the solid every 30 minutes until the solid content meets the standard, then cool down to 100±5℃, and then add dilution.
[0088] The test results of Example 2:
[0089] 1. The test results of the resin technical indicators of this embodiment are as follows: solid content 50.8%, viscosity: 3900 CPS / 25°C, acid value: 2.0 mgKOH / g.
[0090] 2. Carry out paint application experiment, and all other requirements are met.
[0091] 3. Synthesis mechanism: Solution-based free radical polymerization reaction, using the "hunger" drop method to make the molecular weight as uniform as possible, and selecting the appropriate drop time based on the solid content. Too long will affect production efficiency, and too short will affect conversion rate; adding initiator three times is to fully improve the conversion rate. After actual measurement, the conversion rate is 100%.
[0092] 4. The monomer conversion rate is the main factor in process control, which is reflected by measuring the solid content and viscosity. This is because free radical reaction is an irreversible reaction. Usually, when there is more initiator, the resin has a lower viscosity and a lower molecular weight; when there is less initiator, the resin has a higher viscosity and a higher molecular weight; when the reaction temperature is high, the molecular weight is lower and more uniform.
[0093] Embodiment 3:
[0094] The present embodiment provides a hydroxyl acrylic resin suitable for a solar photovoltaic panel backplane coating, comprising the following raw materials in parts by weight:
[0095] Bottom material: 34 g butyl acetate, 6 g propylene glycol methyl ether acetate;
[0096] Mixed monomer drop feed: 17.5 g methyl methacrylate, 12 g n-butyl methacrylate, 9.5 g hydroxyethyl methacrylate, 7.5 g tert-butyl acrylate, 5 g lauryl methacrylate, 5 g isooctyl methacrylate, 0.3 g methacrylic acid, 0.4 g 1,1-bis(tert-butylperoxy)cyclohexane, 0.2 g tert-butyl peroxybenzoate, 4 g butyl acetate;
[0097] Supplementary material 1: 0.15 g of tert-butyl perbenzoate
[0098] Butyl acetate 4 g;
[0099] Additional feed 2: 0.14 g 1,1-bis(tert-butylperoxy)cyclohexane,
[0100] Butyl acetate 2 g;
[0101] Additional feed 3: 0.14 g 1,1-bis(tert-butylperoxy)cyclohexane,
[0102] Butyl acetate 2 g;
[0103] Diluent: 6 grams of butyl acetate.
[0104] A preparation process of a hydroxy acrylic resin suitable for solar photovoltaic panel coatings in this embodiment includes the following steps:
[0105] 1) Add the bottom material into the reactor, stir evenly, raise the reflux temperature of the reactor to 130±5℃, keep it for 10-20 minutes, and prepare to drop the mixed monomer drop material;
[0106] 2) Add the mixed monomer dropwise at a uniform speed over 3-3.5 hours, and keep it under reflux for 1.0 hour after the addition, with the temperature controlled at 130±5℃;
[0107] 3) Add additional material 1 dropwise over 30 minutes, and keep it under reflux for 1.0 hour after the addition is completed. The temperature is controlled at 130±5℃;
[0108] 4) Add additional material 2 dropwise over 15 minutes, and keep it under reflux for 2.0 hours after the addition is completed. The temperature is controlled at 130±5℃;
[0109] 5) Add additional material 3 dropwise over 15 minutes, and keep it under reflux for 2.0 hours after the addition is completed. The temperature is controlled at 130±5℃;
[0110] 6) Cool down to 100±5℃, add the diluted material, stir evenly and test the solid content and viscosity to the qualified range. The qualified range is: solid content: 50±2%, viscosity: 3000-5000CPS / 25℃, acid value: ≤3 mgKOH / g
[0111] The specific process of testing solid content and viscosity is: first measure the solid content. Under normal circumstances, if the solid content is qualified, the viscosity is also qualified. If the solid content does not meet the standard, continue to heat the reflux temperature to 130±5℃, maintain it, measure the solid every 30 minutes until the solid content meets the standard, then cool down to 100±5℃, and then add the dilution solvent.
[0112] The test results of Example 3:
[0113] 1. The test results of the resin technical indicators of this embodiment are as follows: solid content 50.9%, viscosity: 4100 CPS / 25°C, acid value: 2.1 mgKOH / g.
[0114] 2. Carry out paint application experiment, and all other requirements are met.
[0115] 3. Synthesis mechanism: Solution-based free radical polymerization reaction, using the "hunger" drop method to make the molecular weight as uniform as possible, and selecting the appropriate drop time based on the solid content. Too long will affect production efficiency, and too short will affect conversion rate; adding initiator three times is to fully improve the conversion rate. After actual measurement, the conversion rate is 100%.
[0116] 4. The process control is mainly based on the monomer conversion rate, which is reflected by measuring the solid content and viscosity. Because the free radical reaction is an irreversible reaction, usually more initiators have a small resin viscosity and a low molecular weight; less initiators have a large resin viscosity and a high molecular weight; the reaction temperature is high, and the test results of molecular Example 3 are:
[0117] 1. The test results of the resin technical indicators of this embodiment are as follows: solid content 50.9%, viscosity: 4100 CPS / 25°C, acid value: 2.1 mgKOH / g.
[0118] 2. Carry out paint application experiment, and all other requirements are met.
[0119] 3. Synthesis mechanism: Solution-based free radical polymerization reaction, using the "hunger" drop method to make the molecular weight as uniform as possible, and selecting the appropriate drop time based on the solid content. Too long will affect production efficiency, and too short will affect conversion rate; adding initiator three times is to fully improve the conversion rate. After actual measurement, the conversion rate is 100%.
[0120] 4. The process control is mainly based on the monomer conversion rate, which is reflected by measuring the solid content and viscosity. Because the free radical reaction is an irreversible reaction, usually more initiators result in lower resin viscosity and lower molecular weight; less initiators result in higher resin viscosity and higher molecular weight; higher reaction temperature results in lower and more uniform molecular weight. Based on the literature principles and experience, this formula and process were determined, and the application verification proved that the formula and process are reasonable.
[0121] Table 1: Performance index table of hydroxyl acrylic resin of Examples 1-3
[0122]
[0123] The hydroxy acrylic resin of the present invention is suitable for use in solar photovoltaic panel backplane coatings. Regardless of the environment or substrate, the coating has excellent film performance and excellent comprehensive performance. The test report of the solar photovoltaic panel coating produced using the hydroxy acrylic resin of the present invention is shown in Table 2:
[0124] Table 2: Test report of solar photovoltaic panel coating produced by using the hydroxyl acrylic resin of the present invention
[0125]
[0126] The PU coating for solar photovoltaic panels made of the hydroxy acrylic resin of the present invention has been subjected to rigorous application performance tests, and the coating performance has fully met the requirements of customers, and some performance is better than that of the imported resins originally used. From now on, the application of imported resins in solar photovoltaic panel backplane coatings can be said goodbye to, which reduces the cost of backplane coatings and improves the competitiveness of such coatings in the international market.
[0127] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A hydroxylated acrylic resin suitable for solar photovoltaic panel backplane coating, characterized in that The invention comprises the following raw materials in parts by weight: Kettle bottom material: 28-34 parts of butyl acetate, 3-6 parts of propylene glycol methyl ether acetate; Mixed monomer drop feed: 16-18 parts of methyl methacrylate, 12-13 parts of n-butyl methacrylate, 9-10 parts of hydroxyethyl methacrylate, 5-6 parts of tert-butyl acrylate, 3 parts of lauryl methacrylate, 3-5 parts of isooctyl methacrylate, 0.1-0.3 parts of methacrylic acid, 0.4 parts of 1,1-bis(tert-butylperoxy)cyclohexane, 0.1-0.2 parts of tert-butyl peroxybenzoate, 2-4 parts of butyl acetate; Supplementary material 1: 0.1-0.15 parts of tert-butyl perbenzoate and 1-2 parts of butyl acetate; Supplementary material 2: 0.08-0.15 parts of 1,1-bis(tert-butylperoxy)cyclohexane and 1-2.0 parts of butyl acetate; Supplementary material 3: 0.08-0.15 parts of 1,1-bis(tert-butylperoxy)cyclohexane and 1-2.0 parts of butyl acetate; Diluent: 4-7 parts of butyl acetate; The preparation process comprises the following steps: 1) Add the bottom material into the reactor and stir evenly. Raise the temperature of the reactor to reflux at 130±5℃ and keep it for 10-20 minutes. Prepare to drop the mixed monomer material. 2) Add the mixed monomer dropwise at a uniform speed over 3-3.5 hours, and keep it under reflux for 1.0 hour after the addition, with the temperature controlled at 130±5℃; 3) Add additional material 1 dropwise over 30 minutes, and keep it under reflux for 1.0 hour after the addition is completed. The temperature is controlled at 130±5℃; 4) Add additional material 2 dropwise over 15 minutes, and keep it under reflux for 2.0 hours after the addition is completed. The temperature is controlled at 130±5℃; 5) Add additional material 3 dropwise over 15 minutes, and keep it under reflux for 2.0 hours after the addition is completed. The temperature is controlled at 130±5℃; 6) Cool down to 100±5℃, add the diluent, stir evenly and then test the solid content and viscosity to the qualified range. The qualified range is: solid content: 50±2%, viscosity: 3000-5000CPS / 25℃, acid value: ≤3 mgKOH / g.
Citation Information
Patent Citations
Hydroxyl acrylic resin suitable for heat reflection heat insulation coating and preparation method thereof
CN112898473A